Vulnerable Populations, Social Investigations, and Epistemic Justice in Early Victorian Britain - Oz Frankel (Oñati Socio-Legal Series)
Conducted by royal commissions, select committees and the newly established inspectorates, early Victorian social investigations elaborated formats and procedures of public inquiry that left an enduring impact on modern, liberal public spheres in the English speaking world and beyond. This article revisits a few features of 19th Century official investigations, highlighting the rather diverse and contradictory effects these fact-seeking ventures had on British democratic culture. I argue that even as government inquiries confirmed and strengthen social gradations as well as hierarchies of knowledge and expertise, they nevertheless allowed the British lower classes to participate in official discourse as knowers, not just sufferers, and opened new possibilities for dissent and contestations. I highlight the manner in which the investigation itself rather than any consequent legislation or policy touched upon the administration of justice either by emulating court procedures or in terms of its epistemic labor.